The Microcircuit Concept Applied to Cortical Evolution: from Three-Layer to Six-Layer Cortex - Shepherd, Gordon M. (Frontiers in Neuroanatomy, 2011)
Understanding the principles of organization of the cerebral cortex requires insight into its evolutionary history. This has traditionally been the province of anatomists, but evidence regarding the microcircuit organization of different cortical areas is providing new approaches to this problem. Here we use the microcircuit concept to focus first on the principles of microcircuit organization of three-layer cortex in the olfactory cortex, hippocampus and turtle general cortex, and compare it with six-layer neocortex. From this perspective it is possible to identify basic circuit elements for recurrent excitation and lateral inhibition that are common across all the cortical regions. Special properties of the apical dendrites of pyramidal cells are reviewed that reflect the specific adaptations that characterize the functional operations in the different regions. These principles of microcircuit organization provide a new approach to understanding the expanded functional capabilities elaborated by the evolution of the neocortex.